Researching social innovation: is the tail wagging the dog? - Emma L. M. Rhule; Pascale A. Allotey (BMC, 2020)
Abstract Background Social Innovation in health initiatives have the potential to address unmet community health needs. For sustainable change to occur, we need to understand how and why a given intervention is effective. Bringing together communities, innovators, researchers, and policy makers is a powerful way to address this knowledge gap but differing priorities and epistemological backgrounds can make collaboration challenging. Main text To overcome these barriers, stakeholders will need to design policies and work in ways that provide an enabling environment for innovative products and services. Inherently about people, the incorporation of community engagement approaches is necessary for both the development of social innovations and accompanying research methodologies. Whilst the 'appropriate' level of participation is linked to intended outcomes, researchers have a role to play in better understanding how to harness the power of community engagement and to ensure that community perspectives form part of the evidence base that informs policy and practice. Conclusions To effectively operate at the intersection between policy, social innovation, and research, all collaborators need to enter the process with the mindset of learners, rather than experts. Methods - quantitative and qualitative - must be selected according to research questions. The fields of implementation research, community-based participatory research, and realist research, amongst others, have much to offer. So do other sectors, notably education and business. In all this, researchers must assume the mantel of responsibility for research and not transfer the onus to communities under the guise of participation. By leveraging the expertise and knowledge of different ecosystem actors, we can design responsive health systems that integrate innovative approaches in ways that are greater than the sum of their parts.